Intraocular pressure in Japanese diabetic patients - Matsuoka M (Dove Medical Press, 2012)
Masato Matsuoka,1 Nahoko Ogata,2 Kayako Matsuyama,1 Tadanobu Yoshikawa,1 Kanji Takahashi31Department of Ophthalmology, Kansai Medical University, Takii Hospital, Osaka, 2Department of Ophthalmology, Nara Medical University, Nara, 3Department of Ophthalmology, Kansai Medical University, Hirakata Hospital, Osaka, JapanBackground: To determine whether the intraocular pressure (IOP) in diabetic patients is significantly different from that in nondiabetic patients.Methods: The medical records of all patients who were initially examined in the Department of Ophthalmology, Kansai Medical University, Takii Hospital were reviewed. At the initial examination, patients had a detailed interview and underwent a comprehensive ophthalmic examinations. All patients were over 20 years of age and did not have glaucoma.Results: A total of 703 patients were evaluated. The mean (±standard error) IOP of the diabetic patients was 15.5 ± 0.2 mmHg (n = 206), and was significantly higher than the 14.0 ± 0.1 mmHg (n = 497) in the nondiabetic patients (P < 0.0001). The IOP was negatively correlated with age (r = –0.202; P = 0.024) in the diabetic patients and was weakly but significantly correlated with the glycosylated hemoglobin (HbA1c) level (r = 0.240; P = 0.015) in the group with diabetic retinopathy.Conclusion: The significantly higher IOP in diabetic patients and positive correlation of IOP with HbA1c levels in patients with diabetic retinopathy indicate that IOP in diabetic patients is higher, especially in those with poor control of diabetes.Keywords: diabetes mellitus, diabetic retinopathy, intraocular pressure, open-angle glaucoma